Ethical principles in the use of Artificial Intelligence in the financial sector from a European perspective - Parra Rodriguez, Carmen (Studia prawnicze KUL, 2022)
Artificial intelligence (AI) has become part of our daily lives and is a fundamental tool for developing private and professional operations. In this sense, one of the sectors where AI has had the greatest impact has been the financial sector, where it is necessary to establish a regulatory framework to address two fundamental issues to ensure its proper functioning, specifically those aspects that affect digital transparency and neutral algorithms. To address both aspects, the European Union, through its various institutions, has established guidelines for Member States to apply ethical principles that align financial digitalisation with sustainability and the Sustainable Development Goals set out in the 2030 Agenda. These ethical values have been regrouped in a series of principles that must be present in the legislation that regulates future financial operations, ensuring their application within the territory of the European Union. In this regard, financial digitalisation must ensure principles that control risks, creating technologically applicable rules for all sectors that guarantee a level playing field between States without fragmenting the internal market. To this end, they must carry out a prior impartial and external assessment for each operation, based on specific and defined criteria that do not violate fundamental rights or the security standards established in EU law. The methodology used in this article is descriptive, compiling European regulatory projects, taking into account academic studies on ethics in the financial sector.